Preliminary Evaluation of Spraying Quality of Multi-Unmanned Aerial Vehicle (UAV) Close Formation Spraying - Pengchao Chen; Fan Ouyang; Yali Zhang; Yubin Lan (Agriculture, 2022)
Chemical application using unmanned aerial vehicles (UAVs) has received significant attention from researchers and the market in recent years. The concept of using drones for collaborative spraying was proposed by manufacturers for improving intelligence and work efficiency. However, chemical spraying is a professional technology in which spraying quality is the main concern. Using drones to achieve multi-unmanned aerial vehicle formation spraying and evaluating the spraying effect has not yet been reported. In this study, an indoor test platform and two UAVs for field experiments were built. Indoor and outdoor trials of close formation spraying were carried out in Guangzhou and Changji, China from the end of 2018 to 2019, respectively. The droplet density and distribution uniformity of droplets were evaluated from multiple spray overlap areas. It can be seen that simultaneous spraying was better than sequential spraying with the indoor spraying results in the outer fuselage overlap area (S1), and spraying in a short-interval mode can improve the droplet deposition distribution in the overlapping spraying area. Additionally, the droplet distribution result of sequential spraying was better than that of simultaneous spraying in the route center overlap area (S2). Also, the droplet distribution result of the long-interval mode was better than that of the short-interval mode. The uniformity of the droplets’ distribution in two spray width areas (S3) did not change significantly among the treatments.